2016
DOI: 10.2147/ndt.s106123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <em>Astragalus</em> polysaccharides on memory impairment in a diabetic rat model

Abstract: ObjectiveAstragalus polysaccharides (APS) are active constituents of Astragalus membranaceus. In this study, we aimed to investigate the effects of APS on memory impairment in a diabetic rat model and their mechanisms.MethodsA diabetic model was established in 50 male Wistar rats with streptozotocin intra-peritoneal injection. A blood glucose level higher than 16.7 mmol/L obtained 72 hours after the injection was regarded as a successful diabetic model. The modeled rats were divided into model group, high, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Evaluation of the effects of polysaccharides with antidiabetic properties has emerged as an important research field [9]. Our group successfully confirmed the antidiabetic effects of polysaccharide-enriched extractions of Cordyceps militaris , Paecilomyces hepiali , and P .…”
Section: Introductionsupporting
confidence: 57%
“…Evaluation of the effects of polysaccharides with antidiabetic properties has emerged as an important research field [9]. Our group successfully confirmed the antidiabetic effects of polysaccharide-enriched extractions of Cordyceps militaris , Paecilomyces hepiali , and P .…”
Section: Introductionsupporting
confidence: 57%
“…This vicious cycle continues to self-propagate and doesn’t turn off even after the condition is changed to the normal glucose. APS is a Chinese traditional medicine which can suppress the mitochondrial damage and prevent the diabetes (Liu et al 2013; Dun et al 2016). In the current study, we found APS suppressed high glucose-induced metabolic memory in retinal pigment epithelial cells through inhibiting mitochondrial dysfunction-induced apoptosis by regulating miR-195.…”
Section: Discussionmentioning
confidence: 99%
“…The increased leptin level and increased body weight might implicate that leptin resistance was induced by HFZTZ treatment (4). Recent study indicated that APS altered glucose metabolism and decreased insulin resistance in rat with STZ-induced diabetes [ 20 ]. In that work, the potential mechanism of APS on glucose and lipid metabolism, anti-oxidative, insulin resistance and memory deficit in diabetes was studied.…”
Section: Discussionmentioning
confidence: 99%